What hostile and benevolent sexism communicate about mens and womens warmth and competence - Ramos, M. (2019)
Ambivalent sexism theory (Glick & Fiske, 1996) distinguishes between two interrelated forms of sexism: Hostile and benevolent. Although this theory motivated a large body of work examining how endorsement of these views impacts on social interactions and women’s performance, no research has yet examined what these forms of sexism are seen to communicate about men and women. We report three studies examining the image that benevolent and hostile sexist messages are seen to describe (Studies 1 and 2) and prescribe for men and women (Study 3). Results show that both benevolent and hostile sexism were seen to convey that women are and should be less competent than men. Additionally, benevolent sexism was seen as describing and prescribing women to be warmer than did hostile sexism. Across all studies men and women agreed about what the messages communicate about men and women. We discuss the implications of these results for the understanding of how stereotypical beliefs are perpetuated.